ASPEK HUKUM PENGANGKUTAN LIMBAH B-3 LINTAS BATAS NEGARA DALAM HUKUM LINGKUNGAN INTERNASIONAL DAN NASIONAL - Widia Edorita (Fakultas Hukum Universitas Riau, 2013)
In developed countries banned toxicwaste began to be recorded afterproved disastrous. In addition there isa gap for the cost of treating waste B-3 in the developed countries anddeveloping countries. The high cost ofwastewatertreatmentinB-3developed countries in part due to thehigh cost of compliance and strict law.In contrast, the low cost sewagetreatment B-3 in developing countriesdue to the lack of law enforcement.On the other hand, as a result of theconstruction waste requires complextechnology for processing and finaldisposal of hazardous materials isincreasingly narrows with increasingawareness of the importance ofenvironmental protection. Waste-producing countries B-3 and then lookfor the easiest and cheapest way todispose of waste. Poor countries thatare developing targeted for regulationlingkungannnya still weak. Theexistence of import export B-3 wastebetween advanced and developingcountries may be said to have lastedlong enough for the re-emergence ofinternational public awareness of thedangers of pollution is industrialwaste.